A Comparison of the Effectiveness of Interpersonal and Metacognitive Therapies for Social Phobia Disorder - A shirazitehrani; F dirikvand; MA Sepahvandi (Armaghane Danesh Bimonthly Journal, 2016)
Abstract Background & aim: Multidimensional and complex nature of social phobia disorder requires assessment, efficacy and comparison of treatment. The present study aimed to investigate the effectiveness of interpersonal and metacognitive group therapy. in reducing symptoms of social phobia Method: This study is an experimental research and the design of study is pre-test- post-test in which 45 patients suffering from social phobia disorder were selected and randomly assigned to three groups of interpersonal , metacognitive and control . Therapy sessions in groups of 15 people in 8 meeting held .The tools used in this study included the Social Phobia Inventory(SPIN) Social Interaction Anxiety Scale(SIAS) and the Brief Fear Negative Evaluation Scale Revised Version(BFNE-II) and the Structured Clinical Interview for DSM-IV(SCID)is that in the pre-test and post-test were completed by patients.Data was statically analyzed Multivariate Covariance analysis (MANCOVA) and Bonferroni post hoc test to compare difference scale scores pre test-post test variables were used in the experimental and control groups. Results:The results showed that there is significant differences between experimental (interpersonal and metacognitive Therapy) and control group( waiting list) (P<0/001).Also results showed that both interpersonal and metacognitive group therapies were equally effective on the symptom of social phobia disorder, social interaction anxiety and fear of negative evaluation(P<0/001) and its effect size by order of was 0/49, 0/75,0/95. Conclusion: Given the effectiveness of both treatment on social phobia symptoms can be relevant option for clients who go to counseling centers for an effective treatment .